1989
DOI: 10.1136/vr.124.25.651
|View full text |Cite
|
Sign up to set email alerts
|

Flunixin pharmacokinetics and serum thromboxane inhibition in the dog

Abstract: Flunixin meglumine administered orally to beagle dogs at doses of 0.55, 1.10 or 1.65 mg/kg bodyweight was rapidly absorbed to produce maximum mean plasma concentrations of 2.40 +/- 0.70, 4.57 +/- 1.12 and 7.42 +/- 2.07 micrograms/ml, respectively. Thereafter, the plasma concentrations of flunixin fell rapidly to values less than 0.10 micrograms/ml from 24 hours after drug administration at all dosage levels. The maximum mean inhibition of serum thromboxane B2 was 91.5 per cent after the lowest dose of flunixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
4
9
0
Order By: Relevance
“…The presence of blood in faeces in this study is also in accordance with other reports (McKellar et al 1989;D o w et al 1990). This is a normal finding for dogs not receiving any medication (McKellar et al 1989;McKellar et al 1991b).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The presence of blood in faeces in this study is also in accordance with other reports (McKellar et al 1989;D o w et al 1990). This is a normal finding for dogs not receiving any medication (McKellar et al 1989;McKellar et al 1991b).…”
Section: Discussionsupporting
confidence: 82%
“…This is a normal finding for dogs not receiving any medication (McKellar et al 1989;McKellar et al 1991b). However, the presence of the occult blood was a consistent finding after the 3rd and the 4th day of experiment in group I and II respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many evidences show that fever induced by LPS is mediated by a number of endogenous pyrogenic cytokines produced [4,21,22,27]. These pyrogenic cytokines are transported to the thermoregulatory center in the preoptic area, and they stimulate the production of COX-2-dependent prostaglandin (PG) E2, the putative final mediator of the febrile response [15]. The present study demonstrated that LPS caused hyperthermia in both young and adult cats, and that flunixin suppressed dose-dependently hyperthermia induced by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of previous studies of the pharmacokinetics of flunixin in dogs. Plasma pharmacokinetics have been reported by Hardie, Hardee, and Rawlings () for up to 12 hr after IV administration and by McKellar et al () and Ogino, Mizuno, Ogata, and Takahashi () for 24 hr after oral and subcutaneous administration, respectively. The range of levels of detection was 10–50 ng/ml in these studies.…”
Section: Introductionmentioning
confidence: 83%